Natural history and evaluation of Q waves during acute myocardial infarction. - Selwyn, A P (1978)
Serial 72 point praecordial electrocardiographic maps were recorded in 45 patients with uncomplicated acute anterior myocardial infarction. These were analysed and the serial changes in Q waves and ST segments were recorded. Cardiospecific enzyme release curves were constructed from repeated measurements of the plasma activity of the myocardial isoenzyme of creatine kinase (MB CK) during 4 days after the onset of chest pain. The praecordial maps showed that Q waves appeared in the second hour after the onset of chest pain and the development of this electrocardiographic sign was completed within 12 hours. There were complex relations between the development of Q waves, the natural history of ST segment elevation, and the release of MB CK activity. The praecordial area of ST segment elevation at 2 hours was directly related to the fully developed Q wave area at 24 hours after the onset of chest pain. The electrical activity of affected myocardium was lost before peak plasma MB CK activity.